THE IMPACT OF THE DURATION OF ENGAGEMENT IN SPORTS ON THE MORPHOLOGICAL CHANGES OF THE HEART IN ATHLETES DETERMINED BY ECHOCARDIOGRAPHY - Karagjozova, Ivanka; Brazhanska, Mihaela Nestorovska; Gligorovska, Jamina Pluncevic; Spirkoska, Biljana; Ismail, Ljubica Georgievska (Journal of Morphological Sciences, 2024)
Athletes, especially those who have been engaged in sports for a longer time, experience significant physiological adaptations to their cardiovascular system, the most notable of which is the development of the "athlete's heart", a term used to describe morphological changes in the structure of the heart. In order to determine the impact of doing sports on the change of echocardiographic parameters, 2D transthoracic echocardiography was utilized in 54 subjects. Correlations of echocardiographic parameters and characteristics of sporting activities showed that longer participation in sports in years is statistically significantly associated with: greater internal dimension of the left ventricle (LV) in diastole (r = 0.317, p = 0.019; reduction of E/A ratio of trans-mitral flow at early and late filling (r = –0.270, p = 0.048), prolongation of the deceleration time (DT) of the transmitral flow (r = 0.295, p = 0.030), prolongation of the interventricular relaxation time (IVRT) (r = 0.289, p = 0.034) and with borderline significance with an increase in the internal dimension of the right ventricle (r = 0.244; p = 0.76). A greater length of doing sports during the week was statistically significantly associated with greater: internal dimension of the LA (r = 0.297, p = 0.029), indexed LA volume (r = 0.318, p = 0.019;), internal dimension of the LV in diastole (r = 0.347, p = 0.010) and systole (r = 0.485, p = 0.0001), posterior wall thickness in diastole (r = 0.292, p = 0.032);  LV end-diastolic indexed volume (r = 0.310, p = 0.022),  and a lower ratio of pulmonary flow in systole and diastole (S/D, r = –0.282, p = 0.039). The morphological changes of the heart in athletes is the result of long-term physical stress and regular cardiovascular screenings should be conducted in order to ensure an easier distinction between physiological and pathological remodeling of the heart. Key words: athletes, echocardiography, athlete’s heart.